ChemInform Abstract: ortho‐Perfluoroalkylation and Ethoxycarbonyldifluoromethylation of Aromatic Triazenes. Issue 52 (24th December 2013) - Hafner, Andreas; Bihlmeier, Angela; Nieger, Martin; Klopper, Wim; Braese, Stefan
Abstract AgF‐mediated coupling of aromatic triazenes with the silanes (I) and (IV) provides a new, simple, and regioselective approach to ortho‐perfluoroalkylated products.